A Nomogram to Predict Posterior Cranial Fossa Volume Based on Age and Gender - Velpula, Sreekanth; Sadhasivam, Saravanan; Rayapati, Rasi Priya; Nandolia, Khanak K.; Chaturvedi, Jitender; Arora, Rajnish K.; Saxena, Sudhir; Mittal, Radhey Syam (Indian Journal of Neurosurgery, 2025)
The posterior cranial fossa (PCF) is a critical region housing vital structures like the medulla, pons, midbrain, cerebellum, and lower cranial nerves. Several diseases are linked to the posterior fossa, including Arnold–Chiari malformation and posterior fossa tumors. Linear measurement–based formulae are commonly used, as they align well with manual planimetric segmentation, although the latter is labor intensive. Nomograms enhance patient prognosis in various medical fields, including cancer and surgery. However, there is currently no nomogram for predicting the PCF volume (PCFV) based on age and gender in Northern India's population. Our study aims to develop a nomogram using MRI-based volumetric analysis from a Northern Indian tertiary care center.Patients of all age groups, who underwent MRI of the brain at the imaging center in our diagnostic and interventional radiology department and did not have any pathological finding related to posterior fossa, were included in the study. We analyzed 1,132 MR images without any radiologically detectable pathologies.The mean PCFV was 229.95 (±10.16) mL in males and 207.67 (±9.86) mL in females. We developed a nomogram for estimating the PCFV based on age and gender for clinical application.The PCFV varies depending on age and gender. Our findings reveal that the PCFV rises exponentially during the first 2 years of life, followed by a linear increase. The nomogram is a simple technique that may be used in everyday practice to estimate the posterior cerebral fossa volume for a given age and gender. It can be used to study the disease processes affecting the PCF such as including but not limited to Chiari I malformation, Dandy–Walker malformations, cerebellar vermian hypoplasia, and olivopontocerebellar atrophy.
Keywords: magnetic resonance imaging; nomogram; posterior cranial fossa; posterior cranial fossa volume